2018
DOI: 10.1038/s41598-018-32196-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel Hsp90 inhibitor NCT-50 as a potential anticancer agent for the treatment of non-small cell lung cancer

Abstract: Despite the development of advanced therapeutic regimens such as molecular targeted therapy and immunotherapy, the 5-year survival of patients with lung cancer is still less than 20%, suggesting the need to develop additional treatment strategies. The molecular chaperone heat shock protein 90 (Hsp90) plays important roles in the maturation of oncogenic proteins and thus has been considered as an anticancer therapeutic target. Here we show the efficacy and biological mechanism of a Hsp90 inhibitor NCT-50, a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Earlier reports showed that inhibiting Hsp90 can relieve CKS1-induced drug resistance and progression in cancer therapy [13, 14]. Increasing evidences have shown that inhibitors of Hsp90, such as AUY922, 17-AAG, TAS-116, and NCT-50, have significant antitumor activity [1519]. According to the previously study, we speculate that Hsp90 and CKS1 may crosstalk with each other to take part in tumorigenesis, which still need further study.…”
Section: Introductionmentioning
confidence: 57%
“…Earlier reports showed that inhibiting Hsp90 can relieve CKS1-induced drug resistance and progression in cancer therapy [13, 14]. Increasing evidences have shown that inhibitors of Hsp90, such as AUY922, 17-AAG, TAS-116, and NCT-50, have significant antitumor activity [1519]. According to the previously study, we speculate that Hsp90 and CKS1 may crosstalk with each other to take part in tumorigenesis, which still need further study.…”
Section: Introductionmentioning
confidence: 57%
“…However, drug resistance and toxicity confined their clinical applications ( Tomasini et al, 2016 ; Xiong et al, 2019 ). Hsp90, as a chaperone, plays a vital and even decisive role in tumorigenesis and development by assisting 300 client proteins to obtain their correct folding and mature conformation ( Jhaveri et al, 2014 ; Hyun et al, 2018 ). Hsp90 exists with an α-α or β-β homodimer in the cytoplasm, and each monomer consists of three domains.…”
Section: Discussionmentioning
confidence: 99%
“…Among the client proteins, 48 proteins play an important, even decisive role in tumorigenesis and development, such as transmembrane tyrosine kinase, steroid receptors, and cell cycle regulators, etc. ( Jhaveri et al, 2014 ; Hyun et al, 2018 ). Hsp90 N inhibitors lead to multiple misfolded or immature client proteins to be degraded by the ubiquitin protease complex pathway ( Chen et al, 2014 ), which involves simultaneous intervention of multiple potential antitumor target proteins and a “multipoint attack” on the tumor to achieve favorable therapeutic efficacy ( Chehab et al, 2015 ; Dutta Gupta et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it reduces the likelihood of the tumor acquiring resistance to any single therapeutic pathway and is a major advantage upon other agents (Banerji, 2009). However, HSP90 inhibitors such as 17-AAG have not reached clinical trials beyond phase III, due to minimal effects and toxicity, especially liver toxicity (Hyun et al, 2018). Therefore, the combination with other agents, for instance HDACi, could be a promising alternative, in order to reduce the effective concentration of HSP90 inhibitors.…”
Section: Hdac Inhibitors and Hsp90 Inhibitorsmentioning
confidence: 99%